Peran Ekonomi Kreatif dalam Bingkai Ekonomi Islam di Desa Tambakroto Kajen Pekalongan - Fitri Kurniawati (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2021)
Abstract : Creative economy is actually an economy based on local wisdom. When combined with Islamic economics, it will become an empowerment activity that sustains the community. Empowerment as a process of searching (research) to find the best way in solving problems faced by the community. The method used in this research is descriptive qualitative. One of the problems in Tambakroto Village, Kajen District, Pekalongan Regency, is that many villagers are not aware of the potential around them which they might use as additional resources as well as additional or new livelihood innovations. Therefore, the solution to this problem is counseling and creative economic training to residents of Tambakroto Village, Kajen District, Pekalongan Regency. The results of the counseling and training activities for the villagers made them aware of the potential around them and raised the creativity of the residents and opened up more business opportunities for the residents of Tambakroto Village, Kajen District, Pekalongan Regency to increase their daily income. Keywords : Creative Economy, Empowerment, Islamic Economy, Economic Awareness